Evaluasi Penggunaan Obat Pada Pasien Diabetes Melitus Tipe 2 di RSUD dr. H. Slamet Martodirdjo Pamekasan - Norcahyanti, Ika; Rahman, S. Nadya Riskia; Aryani, Dhita Evi (Journal of Agropharmacy, 2026)
Type 2 diabetes mellitus (T2DM) is the most prevalent form of diabetes, accounting for approximately 90% of all cases. Indonesia ranks sixth globally in diabetes prevalence, with national rates rising from 6,9% to 10,9%. Understanding drug utilization patterns can empower healthcare providers to optimize treatment. At RSUD dr. H. Slamet Martodirdjo Pamekasan, T2DM is among the top five diagnoses with highest prevalence in 2018. This observational descriptive study with a retrospective cross-sectional design evaluated drug use in 61 T2DM inpatients (January-June 2018) using a Drug Related Problems (DRPs) approach. Patient characteristics, drug utilization profiles, and DRP categories were analyzed descriptively from medical records. The majority of patients were male (50,82%), adults aged 25-64 years (80,33%), covered by BPJS insurance (88,52%), with hypertension as the most common comorbidity (30,51%). Drugs for the alimentary tract and metabolism were most frequently prescribed (32,15%), with metamizole injection having the highest individual use frequency (11,68%). A total of 238 DRP events were identified in 56 patients: drug interactions (54,20%), overdosage (16,39%), subtherapeutic dosage (15,13%), untreated indication (8,82%), and drug use without indication (5,46%). Drug interactions predominated, with the most frequent being ceftriaxone–Ringer Lactate (14 events, major), ciprofloxacin–insulin aspart (8 events, moderate), and sucralfate–furosemide (5 events, moderate). Standardization of medical records, prescribing practices, and active clinical pharmacist involvement are recommended to minimize DRPs in T2DM inpatient care.